Association between skeletal muscle and left ventricular mass in patients with hyperthyroidism - Liu, Zhenchao; Liu, Guang; Wang, Yanzhi; Zheng, Chongwen; Guo, Yunliang (Frontiers in Endocrinology, 2024)
Objective This study aims to investigate the relationship between skeletal muscle and left ventricular mass (LVM) in patients with hyperthyroidism, providing theoretical and data-based foundations for further research on the interaction between secondary muscle atrophy and cardiac remodeling. Methods A retrospective data collection was conducted, including 136 patients with hyperthyroidism (Study group) and 50 healthy participants (control group). The Study group was further divided into Group A (high LVM) and Group B (low LVM) based on LVM size. Multiple linear regression analysis was performed to examine the correlation between skeletal muscle and LVM, with model evaluation. Based on the results, further nonlinear regression analysis was conducted to explore the detailed relationship between skeletal muscle and LVM. Results Compared to the control group, the Study group exhibited significantly lower LVM, skeletal muscle mass index (SMI), and skeletal muscle mass (SMM) (P<0.05). Within the subgroups, Group A had significantly higher SMI, SMM, and hand grip strength compared to Group B (P<0.05). The results of the multiple linear regression showed a certain correlation between SMI (β=0.60, P=0.042, 95% CI=0.02~1.17) and hand grip strength (β=0.34, P=0.045, 95% CI=0.01~0.67) with LVM. However, the residuals of the multiple regression did not follow a normal distribution (K-S=2.50, P<0.01). Further results from a generalized linear model and structural equation modeling regression also demonstrated a correlation between SMI (β=0.60, P=0.040, 95% CI=0.03~1.17) (β=0.60, P=0.042, 95% CI=0.02~1.17) and hand grip strength (β=0.34, P=0.043, 95% CI=0.01~0.67) (β=0.34, P=0.045, 95% CI=0.01~0.67) with LVM.Patients with hyperthyroidism may exhibit simultaneous decreases in LVM, SMM, and SMI. The LVM in patients is correlated with SMM and hand grip strength, highlighting the need for further exploration of the causal relationship and underlying mechanisms. These findings provide a basis for the prevention and treatment of secondary sarcopenia and cardiac pathology in patients with hyperthyroidism.